Dislocation generation in GaAs crystals grown by the vertical gradient freeze method - (:unkn) unknown (ELSEVIER SCIENCE SA, 2000)
The objective of this study is to develop a numerical model for predicting the dislocation density in GaAs crystals grown by the vertical gradient freeze (VGF) method at different growth parameters, such as the crystal growth rate, crystal diameter, and imposed temperature gradients on the crucible. Dislocation is an important defect in semiconductors. The production of near-dislocation-free crystal demands the crystal growth parameters to be perfectly adjusted to the properties of the growing material. The relationship between the crystal growth parameters and final dislocation density needs to be understood for the production of low dislocation-density crystals. In this study, dislocation densities in crystals grown by different parameters and growth directions has been calculated and compared with experimental findings. This investigation will provide valuable information for understanding the influence of growth parameters on final GaAs crystal quality. (C) 2000 Elsevier Science S.A. All rights reserved.
Keywords: dislocation generation; GaAs; semiconductors; single crystals growth; vertical gradient freeze method; MODEL; PREDICTION; DYNAMICS; MELT